(untitled) (AYUSHDHARA, 2019)
Siddha system of medicine has its unique way like any other medical systems in this world. Subacromial impingement syndrome (SAIS) is the most common disorder of shoulder. SAIS encompasses a spectrum of subacromial space pathologies including partial thickness rotator cuff tears, rotator cuff tendinosis, calcific tendinitis, and subacromial bursitis. The main consequences of SAIS are functional loss and disability. SAIS is correlated with “Kumbavatham” which is one of the Vatha diseases mentioned in the Siddha system of medicine. Material and Methods: A 42 year old married female patient who is a home maker was admitted in the IPD of Sirappu Maruthuvam Department at National Institute of Siddha for 45 days with complaints of pain present in the left shoulder joint, difficulty to combing and wearing of her dress and buttons, difficulty to raise her left upper limb and pain aggravated during night time for the past 2 years. Special Varmamthadaval procedure was applied over the passage of Varmam points in the affected limb and was undergone for 10 days on alternative days basis. Result: After treatment the pain in the left shoulder was considerably reduced, she was able to wear her dress, buttoning was easy and was able to fully raise her left upper limb. Conclusion: Special Varmamthadaval therapy with fomentation treatment is a very effective external therapy in Siddha. It is found to be more effective especially in musculo skeletal disorders. In SAIS, Shoulder Impingement Syndrome was relieved and also pain was relieved considerably by Siddha external therapy.